2009
DOI: 10.1590/s1415-47572009005000003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the genes UL1 through UL7 of the duck enteritis virus and other herpesviruses of the subfamily Alphaherpesvirinae

Abstract: The nucleotide sequences of eight open reading frames (ORFs) located at the 5' end of the unique long region of the duck enteritis virus (DEV) Clone-03 strain were determined. The genes identified were designated UL1, UL2, UL3, UL4, UL5, UL6 and UL7 homologues of the herpes simplex virus 1 (HSV-1). The DEV UL3.5 located between UL3 and UL4 had no homologue in the HSV-1. The arrangement and transcription orientation of the eight genes were collinear with their homologues in the HSV-1. Phylogenetic trees were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…The DEV gene arrangement and content in this region ( fig. 2 ) showed differences from other genes in previously reported UL regions [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The DEV gene arrangement and content in this region ( fig. 2 ) showed differences from other genes in previously reported UL regions [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 82%
“…Generally, the arrangement of partial genes in the UL region of the DEV genome is collinear with homologues in HSV-1, and phylogenetic analysis of most b genes in the DEV UL region has shown that DEV has a close relationship to members of Mardivirus [10][11][12][13][14] . In the present study, we report sequences in the leftmost region of DEV UL and the molecular characteristics of predicted genes in this region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations